South Africa : Staff Report for the 2002 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2003)
This 2002 Article IV Consultation highlights that in 2001, the South African economy felt the impact of a slowdown in global economic activity, which interrupted the modest upturn that started late in 1998. Driven mainly by a contraction in overseas demand that lowered export prices and volumes, real GDP growth fell to 2.2 percent in 2001 from 3.4 percent in 2000. Activity reached a trough in the third quarter of the year, with GDP growth slowing to about 1 percent at an annualized rate and unemployment rising further from already high levels.